The Influence of Casting Machine Speed in Cellulose Acetate Membrane Preparation - Luqman Buchori (International Journal of Science and Engineering, 2010)
Membranes are being increasingly used as a valuable separation tool in laboratory as well as in industrial processes.  Continual  development  of  new  membrane  materials  is  crucial  to  sustain  and  expand  the growing  interest  in  this  technology  and  modern  polymer  chemistry  is  highly  proficient  in  tailoring polymers with desired properties such as increased mechanical, thermal and chemical stability. Cellulose acetate (CA) is one of the membrane polymers that has been used for aqueous based separation and used as both reverses osmosis (RO) and ultrafiltration (UF) membranes.   This paper presents investigation of influence of casting machine speed in membrane preparation. CA is used in this study. That was CA-398-30 with average  acetyl  content  39.8 wt %.  Non solvent  used is water  and the  solvent  is 99.7 %  organic Dimethyl Sulfoxide  (DMSO). The homogenous CA/DMSO  solutions were prepared by dissolving CA  in DMSO solvent. The CA concentration were varied 13 and 16 % while casting solution speed were varied from  20  to  80  mm/sec  with  distance  cutting  machine  were  fixed  at  14  cm.  In  addition,  non  solvent  in coagulation  bath  also  were  varied  by  100  %  water  and  10  %  DMSO  in  water.  The results  of  this experiment   describe   effect   of   casting   machine   speed   to   water   permeability.   The   effect   of   CA concentration  to  water  permeability  shows the  adversative result  between 13 and  16 %  CA  in  100 non solvent water. The similar result also observed in 10 % DMSO in water.